Write an equivalent expression for the following x + x + x + 2x + x (x + 2) + (x + 2) y + y + y + y + 10 + y + 1

Question

Write an equivalent expression for the following
x + x + x + 2x + x
(x + 2) + (x + 2)
y + y + y + y + 10 + y + 1

in progress 0
Lệ Thu 6 months 2021-08-06T15:44:32+00:00 1 Answers 9 views 0

Answers ( )

    0
    2021-08-06T15:46:17+00:00

    Answer:

    6x, 2x + 4, 5y + 11

    Step-by-step explanation:

    x + x + x + 2x + x = 6x

    (x + 2) + (x + 2) = 2x + 4

    y + y + y + y + 10 + y + 1 = 5y + 11

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )